PKM Peningkatan Pengetahuan Pada Ibu Nifas Menyusui Tentang Manfaat Rebusan Daun Torbangun Terhadap Peningkatan Produksi ASI - Pardede, Desika Wali; Damanik, Nanayani; Arisman, Yessi (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Breast Milk Water (breast milk) is an essential infant nutrient, yet many nursing mothers face the challenge of suboptimal breast milk production. The leaves of Torbangun (Coleus amboinicus Lour) are traditionally known as galactogogues. The present study was to test the influence of torbangun leaf decoction in increasing milk production. The study used a quasi-experimental with a control group prestest-posttest design. A total of 34 lactating mothers were divided into an experimental group (17 people) and a control group (17 people). Milk production before and after administration of torbangun leaf decoction on the experimental group from the statistical test results of the Independent T-test was obtained the mean (mean) The milk production of the respondents before the administration of the intervention in the form of torbangun leaf decoction was 30.00, and the mean ASI production of the respondents was 69, p value after the intervention1 0.000 at an alpha (?) of 5%.